2018
DOI: 10.17706/jsw.13.10.520-532
|View full text |Cite
|
Sign up to set email alerts
|

Requirements Engineering in Global Software Development: A Survey Study from the Perspectives of Stakeholders

Abstract: Global software development (GSD), where software teams are located in different parts of the world, has become increasingly popular. However, GSD involves issues such as geographical distance, cultural diversities, differences in time zones, and language barriers amongst stakeholders, making it different from collocated software development, and requirements engineering (RE) is very much affected by these issues. To examine what stakeholders think about the impact of these factors on the different activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…According to Niazi et al [9], the requirements engineering process is not standardized in the context of a geographically distributed environment. However, due to the dispersed nature of development in the context of the GSD, the practitioners faced several problems, and they found that fluent communication is one of the major barriers [9], [15], [31]. Niazi et al [9] indicated that the majority of the organizations that carried their development activities across the globe followed an informal RE process.…”
Section: A Finding Of Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Niazi et al [9], the requirements engineering process is not standardized in the context of a geographically distributed environment. However, due to the dispersed nature of development in the context of the GSD, the practitioners faced several problems, and they found that fluent communication is one of the major barriers [9], [15], [31]. Niazi et al [9] indicated that the majority of the organizations that carried their development activities across the globe followed an informal RE process.…”
Section: A Finding Of Literature Reviewmentioning
confidence: 99%
“…Shafiq et al [5] and Thanasankit [4] highlighted the importance of standards and procedures for the RE process while adopting a software outsourcing paradigm. Various barriers are associated with software outsourcing, particularly that related to the requirements engineering process [15], [30]. A study conducted by Khan et al [38] indicated that the barriers of the RE process are the root causes of project failure.…”
Section: A Finding Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant work has been conducted to understand RE in the GSD [15][16][17]. However, no work has been carried out that identifies barriers that influence the RE process in GSD projects.…”
Section: Introductionmentioning
confidence: 99%